Perceived Supervisor Support and Turnover Intention: A Meta-Analysis Study - Tri Astuti; Avin Fadilla Helmi (Buletin Psikologi, 2021)
Employees intending to resign are commonly due to material matters, such as lack of salary or incentives. Evidently, moral matters, e.g., supervisor support, implies to affect the turnover intention in an organization. Studies pertaining the effect of these two variables to intention to resign report mixed result. For example, several studies report direct and significant effect of these two variables to intention to resign, while otherstudies report the contrary. This study aimed to investigate the direct influence of perceived supervisor support on employee turnover intention through a meta-analysis method. There are 17 articles and 20 studies, ranging from 2007 to 2019 being analysed, of which 60% were published in accredited international journals, and the remaining 40% were published in international journals. Aggregate number of respondents of the studies amounted to 10,079 people from all industrial sectors, such as manufacturing, healthcare, hospitality industry, education, and social services in several countries, such as the Philippines, China, India, Pakistan, Turkey, Norway, and the United States. This study employed data from the standardized beta coefficient using an open-source program data analysis application of Mplus. The study results found that perceived supervisor support did not directly affect employee turnover intention. The study can be used as a reference for similar studies to compare other interrelated variables.